One anti-tumour C21 steroidal glycoside from Cynanchum wallichii Wight - Shuo Liu; Yong Cui; Qianxiaochuan Wang; Jiahui Wang; Yating Zhang; Lina Fang (Natural Product Research, 2026)

The impact of digital factor allocation on urban resilience under energy constraints in China - Sisi Zhang; Yingxin Su; Yating Zhong; Qi Cui (Environment, Development and Sustainability, 2026)

Piperazine concentration-driven effect fabricated NF membrane with ambidextrous selectivity for SO42−/Cl− and Mg2+/Na+: Mechanism and efficient water purification - Hailin Chang; Shilei Fu; Ziao Zhang; Yating Hu; Zijian Cui; Jun Ma; Kexin Hou; Xiaobin Tang; Guibai Li; Heng Liang (Desalination, 2025)

Interactions between raw dark tea chemistry and dominant fungi shape Hei brick tea quality - Yating Guo; Haijing Cui; Xinxin Wang; Haowei Guo; Xinyu Feng; Anran Yan; Yani Pan; Lixin He; Liping Liu; Kexin Zhang; Hua Fang; Hesham R. El-Seedi; et al. (International Journal of Food Microbiology, 2025)

Enhanced NIR-triggered photo-to-chemo conversion based on plasmonic heterojunction nanozyme for tetra-hybrid antineoplastic therapy - Yunxiang Zhang; Derui Xu; Xiaohui Wang; Hongsheng Shen; Bin Chen; Qian Liu; Yating Cui; Xinmiao Hou; Siyu Zhao; Qing Song; Xichuan Li; Xinghua Jin (Chemical Engineering Journal, 2025)

Methyl jasmonate attenuates chilling injury of prune fruit by maintaining ROS homeostasis and regulating GABA metabolism and energy status - Yating Zhao; Yingjie Wu; Xuan Zhang; Xuan Zhu; Yuanyuan Hou; Jianye Chen; Kuanbo Cui; Xuewen Li; Wenxin Wu (Postharvest Biology and Technology, 2025)

Effects of Wildfire on the Adsorption-Desorption of Soil Free Amino Acids in a Dahurian Larch Forest in Northeast China - Xinxin Zheng; Yun Zhang; Yating Deng; Xiaoyang Cui (Journal of Soil Science and Plant Nutrition, 2024)

Resilience analysis of the RCEP shipping network - Jiaguo Liu; Yating Fu; Kangkang Han; Ying Cui (Ocean & Coastal Management, 2024)

Multi-omics association study of hexadecane degradation in haloarchaeal strain Halogranum rubrum RO2-11 - HeLang Huang; CaiYun Xie; ZiYuan Xia; ZhaoYong Sun; YaTing Chen; Min Gou; YueQin Tang; HengLin Cui; XiaoLei Wu (Environmental Research, 2024)

Long-Term Spatiotemporal Characteristics of Ulva prolifera Green Tide and Effects of Environmental Drivers on Its Monitoring by Satellites: A Case Study in the Yellow Sea, China, from 2008 to 2023 - Yating Zhan; Zhongfeng Qiu; Yujun Wang; Yiming Su; Yin Li; Yanmei Cui; Shuai Qu; Peng Wang; Xin Rong (Journal of Marine Science and Engineering, 2024)
Ulva prolifera (U. prolifera) green tide outbreaks have occurred in the Yellow Sea of China for many years, causing serious losses to marine ecology and the marine economy. The monitoring and tracking of U. prolifera green tide is a crucial aspect of marine ecological disaster prevention and control management. This paper aims to investigate the spatiotemporal distribution changes in U. prolifera green tide in the Yellow Sea throughout its life cycle. A survey of the Yellow Sea from 2008 to 2023 was conducted using multi-source remote sensing images. Long-term monitoring and analysis of U. prolifera revealed the evolution process of the green tide, including the early development, outbreak, decline, and extinction stages, considering time, space, and frequency of occurrence. Additionally, this study examined peak coverage change patterns over the past 16 years and analyzed the influence of environmental factors such as sea surface temperature and sea surface wind field on the development of U. prolifera. The research results serve as a valuable reference for the monitoring, early warning, and scientific prevention and control of U. prolifera green tide in the Yellow Sea, as well as other similar marine disaster areas.

Lithium Chloride Promotes Endogenous Synthesis of CLA in Bovine Mammary Epithelial Cells - Jiayi Liu; Jinglin Shen; Jinxin Zong; Yating Fan; Junhao Cui; Dongqiao Peng; Yongcheng Jin (Biological Trace Element Research, 2024)

Recent advance in high-intensity ultrasound modification of blue food protein: Mechanisms, functional properties and structural alterations - Zhihui Yu; Yating Gao; Xinyi Jia; Shuai Cui; Li Ma; Dan Zheng; Xin Li; Long Li; Lixin Zhang; Yisheng Chen (Trends in Food Science & Technology, 2024)

Introducing Ni co-cations to simultaneously maintain a high NOx uptake capacity and improve the hydrothermal stability of Pd/SSZ-13 for low-temperature NO adsorption - Jinhuang Cai; Yating Huang; Xiaomin Wu; Zhiwei Huang; Huazhen Shen; Kai Cui; Zhenguo Li; Guohua Jing; Johannes W. Schwank; Huawang Zhao (Chemical Engineering Journal, 2023)

Low-dose BPA and its substitute BPS promote ovarian cancer cell stemness via a non-canonical PINK1/p53 mitophagic signaling - Xiaoyu Yuan; Kelie Chen; Fang Zheng; Sinan Xu; Yating Li; Yuwei Wang; Heng Ni; Fang Wang; Zhenyan Cui; Yuheng Qin; Dajing Xia; Yihua Wu (Journal of Hazardous Materials, 2023)

Effects of Ulva prolifera dissipation on the offshore environment based on remote sensing images and field monitoring data - Longxiao Zheng; Mengquan Wu; Jie Zhao; Shaopeng Luan; Dongliang Wang; Wei Jiang; Mingyue Xue; Jiayan Liu; Yating Cui (Acta Oceanologica Sinica, 2023)

Water-based green and sustainable extraction protocols for value-added compounds from natural resources - Yating Jin; Di Hu; Qianqian Chen; Cui Shi; Jing Ye; Zhiyuan Dai; Yanbin Lu (Current Opinion in Green and Sustainable Chemistry, 2023)

Hippocampal Iron Accumulation Impairs Synapses and Memory via Suppressing Furin Expression and Downregulating BDNF Maturation - Yating Zhang; Xue Bai; Yi Zhang; Shanshan Yao; Yiduo Cui; Lin-Hao You; Peng Yu; Yan-Zhong Chang; Guofen Gao (Molecular Neurobiology, 2022)

Correction to: Linarin Protects against Cadmium-Induced Osteoporosis Via Reducing Oxidative Stress and Infammation and Altering RANK/RANKL/OPG Pathway - Yating Yang; Ruining Cheng; Jingyun Liu; Jing Fang; Xiaojing Wang; Yingxue Cui; Pan Zhang; Bin Du (Biological Trace Element Research, 2022)

Linarin Protects against Cadmium-Induced Osteoporosis Via Reducing Oxidative Stress and Inflammation and Altering RANK/RANKL/OPG Pathway - Yating Yang; Ruining Cheng; Jingyun Liu; Jing Fang; Xiaojing Wang; Yingxue Cui; Pan Zhang; Bin Du (Biological Trace Element Research, 2022)

Genetic structure and polymorphism analysis of Xinjiang Hui ethnic minority based on 21 STRs - Qiong Lan; Jiangang Chen; Yuxin Guo; Tong Xie; Yating Fang; Xiaoye Jin; Wei Cui; Yongsong Zhou; Bofeng Zhu (Molecular Biology Reports, 2018)